Asian soybean rust: etiology and control - Pelin, Cauê (2020)
The Asian rust of soybean, caused by fungal Phakopsora pachyrhizi, is considered the main soybean disease in Brazil. This disease is responsible for productive losses of up to 90% under ideal conditions for its development. This technical report aims to systematize information regarding Asian soybean rust, as well as its management. Key techniques include cultural, chemical and genetic management, which should be applied together to control the disease. Preventive practices are extremely important and should not be ignored. These practices should be applied in conjunction with the use of fungicides, where mixing active ingredients contributes for disease management.